Predicting saturated fat consumption: Exploring the role of subjective well-being - Mullan, Barbara; Xavier, Kristina (Routledge, 2013)
Consumption of saturated fat (SF) is associated with obesity, cardiovascular disease and cancer; which are among the leading causes of death in Australia and worldwide. A causal relationship between subjective well-being and positive health outcomes has been established, although few studies have specifically focused on health-enhancing or health-risk behaviours. The aim of this research was to develop an improved understanding of the processes underlying SF consumption by exploring the relationship between subjective well-being and SF consumption, within the Theory of Planned Behaviour framework. Questionnaires related to the TPB variables, subjective well-being and SF intake were administered online to 96 participants. Perceived behavioural control (PBC) was found to be a significant predictor of intention to limit SF intake. Intention and PBC accounted for 25% of variance in behaviour; with PBC the only significant predictor of SF consumption. While subjective well-being variables were not significant unique predictors of SF consumption, these variables contributed an additional 2% to the prediction of behaviour, and this model was significant. The addition of subjective well-being to the TPB is novel and the results partially support the potential of subjective well-being in improving the prediction of this health-risk behaviour. Future research will need to replicate and extend these preliminary findings before such a framework may be translated into an intervention targeting SF consumption.